The impact of intellectual capital disclosure on cost of equity capital: A case of French firms - Mohamed Ali Boujelbene; Habib Affes (Journal of Economics, Finance and Administrative Science, 2013)
The purpose of this paper is to examine empirically the impact of intellectual capital disclosure (IC) on cost of Equity capital. The empirical research is based on companies listed in the French SBF 120 stock market index. The findings confirm our hypotheses that stipulate the existence of a significant and negative association between intellectual capital disclosure with its two components (human capital, structural) and the cost of equity. However, the negative impact of the relational capital disclosure is not validated. The results in this paper are of considerable importance to both policy makers and firms. In fact, the understanding of the impact of Intellectual capital disclosure on cost of equity capital helps policy makers in the evaluation of the costs and benefits of disclosure. Moreover, with regard to managers of firms, the results show the benefit of enhanced IC disclosure regarding the reduction in their cost of capital. This study is one of the very first to provide empirical evidence of the association between Cost of equity capital and the level of disclosure in the three individual intellectual capital categories (human; structural and relational capital). – – El objetivo de este trabajo es examinar el impacto de la divulgación del capital intelectual (CI) sobre el coste del capital social. La investigación empírica se basa en las empresas que figuran en el índice bursátil francés SBF 120. Los hallazgos confirman nuestras hipótesis, según las cuales existe una asociación significativa y negativa de la divulgación del capital intelectual con sus dos componentes (capital humano y estructural) y el coste de los fondos propios. No obstante, no se ha confirmado el impacto negativo de la divulgación del capital relacional. Los resultados de este trabajo tienen una importancia considerable tanto para los legisladores como para las empresas. De hecho, la comprensión del impacto de la divulgación del capital intelectual sobre el coste del capital social ayuda a los legisladores a evaluar los costes y beneficios de la divulgación. Además, con respecto a los gerentes de las empresas, los resultados muestran los beneficios de la mayor divulgación de CI en cuanto a la reducción de su coste de capital. Este estudio es uno de los primeros en proporcionar pruebas empíricas de la asociación entre el coste del capital social y el nivel de divulgación en las tres categorías de capital intelectual individual (capital humano, estructural y relacional).
Keywords: M41; 330; Disclosure; Intellectual capital; French companies; Cost of Equity Capital; Divulgación; Capital intelectual; Empresas francesas; Coste del capital social